2017
DOI: 10.1177/1539449217743457
|View full text |Cite|
|
Sign up to set email alerts
|

Validity of the Turkish Occupational Self Assessment for Elderly Individuals

Abstract: Occupational therapy practices in Turkey are increasing each year, but rehabilitation practitioners working in the occupational therapy field have limited instruments. The aim of this study was to analyze the validity of the Turkish version of the Occupational Self Assessment (OSA), which is based on the Model of Human Occupation. The data were analyzed using exploratory and confirmatory factor analyses to determine construct validity. The Turkish OSA was administered with the World Health Organization Quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…Studies on activity and participation have gained importance in www.e-agmr.org our country. Pekcetin et al 21) showed occupational competence and values in older Turkish individuals. Similarly, Akyurek et al 22) emphasized the importance of community participation among people with disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on activity and participation have gained importance in www.e-agmr.org our country. Pekcetin et al 21) showed occupational competence and values in older Turkish individuals. Similarly, Akyurek et al 22) emphasized the importance of community participation among people with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Floor and ceiling effects were defined as 15% or more of the participants with the lowest and highest possible scores on the Ox-PAQ, respectively. 21)…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamıza katılan bireylerin yaşam kaliteleri yüksek bulunmuştur ve bu sonuç yaşlı bireylerin yaşam kalitelerinin incelendiği önceki çalışmaları desteklemektedir (12,25).…”
Section: Discussionunclassified
“…After completing the instrument, the therapist asks the client to indicate the four items that are their highest priorities for change (Baron, 2006). The Turkish validity study of the scale was conducted (Pekçetin et al, 2018). The researcher showed that the model fit the data according to the indices of relative fit (RMSEA = 0.099, CMIN/DF = 2.142).…”
Section: Methodsmentioning
confidence: 99%